The Effect of Animal Bipedal Posture on Perceived Cuteness, Fear, and Willingness to Protect Them - Prokop, Pavol; Zvaríková, Martina; Zvarík, Milan; Pazda, Adam; Fedor, Peter (Frontiers in Ecology and Evolution, 2021)
Human-animal relationships have long been the subject of controversy because they are shaped by several cultural, inter-individual, and evolutionary factors. Understanding these relationships, however, is important to optimize conservation efforts. There is agreement that perceived similarity between animals and humans is associated with more positive attitudes. The human-animal similarity could be caused by phylogenetic closeness. We hypothesized that bipedal posture of an animal may be perceived as a cue of phenotypic similarity with humans. We examined this topic by comparing perceived cuteness, fear and willingness to protect animals differing in body posture, body size, and phylogenetic closeness with humans on a sample of N = 349 Slovak participants. We found that bipedal posture enhanced perceived cuteness, but this effect was most pronounced in small-bodied animals, particularly those with direct eye contact. Phylogenetically close and small-bodied species (e.g., small mammals) received greater conservation support than phylogenetically distant species (e.g., invertebrates). However, anthropomorphic looking animals received greater conservation support, suggesting that pictures of animals that more closely resemble humans can be used in conservation campaigns.